Dosimetry study in an X-ray irradiator : Monte Carlo simulations and experimental results on radio-photoluminescence samples - Alem, Abrham (2023)
Matter’s exposure to ionizing radiations leads to a variety of possible interactions. Depending on the specific interaction type, energy can be deposited into matter via different mechanisms. The quantification of the absorbed dose in matter is crucial to monitor the radiation levels and asses radiation effects in matter in different application areas such as radiation therapy, particle accelerators, space applications, and high-energy nuclear radiation facilities. The stochastic nature of radiation-matter interaction often requires the use of Monte Carlo tools in dosimetry applications. In the present work, a commercial X-ray irradiator is modeled using PHITS general Monte Carlo tool, aiming at verifying the possibility of using it for the irradiation of various types of macroscopic samples at high doses, ranging between the kGy and the MGy levels. Simulated particle fluence spectra evidence that the effect of the Be exit window, often included in the X-ray tube design as a first filter and different additional thicknesses of Al and Cu filters can be effectively used to attenuate low energy photons, often responsible for high dose inhomogeneities in thick samples. To assess the feasibility of using the available X-ray spectra for the irradiation of different samples having thicknesses up to several millimetres, the absorbed dose across the sample’s depth for different materials such as Radio Photoluminescent (RPL) glass dosimeters, silica for comparison purposes and water as reference was calculated using PHITS, with a sample depth spatial resolution of 0.1 mm and 10 µm. The homogeneity of the absorbed dose in the RPL dosimeter volume can be improved by the use of appropriate types of filters and it is found that 1.5 mm, 3 mm thick Al and 1.5 mm thick Cu filters can improve the dose homogeneity to 30 %, 15 %, and 8 % deviation from the average dose value respectively in the selected samples. By using a combination of the readout of PTW soft X-ray ionization chamber, normally used for dose rate calibration in the irradiation facility, and the realized simulations, the absorbed dose was calculated for 8 RPL glass samples irradiated in the MOPERIX X-ray irradiator in the frame of another study. The calculated doses are in good agreement with the corresponding experimental values, which were measured in the European Organization for Nuclear Research (CERN) readout systems, allowing a validation of the used methodologies and the estimation of usable conversion factors.